2017
DOI: 10.1038/onc.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 downregulation mediated by DNMT3b contributes to nickel malignant transformation of human bronchial epithelial cells via modulating PHLPP1 transcription and HIF-1α translation

Abstract: Long noncoding RNAs (lncRNAs) are emerging as key players in various fundamental cellular biological processes, and many of them are likely to have functional roles in tumorigenesis. Maternally expressed gene 3 (MEG3) is an imprinted gene located at 14q32 that encodes an lncRNA, and the decreased MEG3 expression has been reported in multiple cancer tissues. However, nothing is known about the alteration and role of MEG3 in environmental carcinogen-induced lung tumorigenesis. Our present study, for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 49 publications
5
105
0
Order By: Relevance
“…The patient characteristics are shown in Supplemental Table 1 (supplemental material available online with this article; https://doi.org/10.1172/JCI96218DS1). As shown in Figure 1A, the microarray analysis identified 158 upregulated and 142 downregulated lncRNAs from 7,419 analyzed lncRNAs in the MIBC tissues, including CASC9, MIAT, MEG3, and LINC01133, which are associated with human cancer progression (25)(26)(27)(28). Additionally, one lncRNA (LINC00958, RefSeq accession number NR_038904), Figure 1.…”
Section: Blacat2 Overexpression Correlates With Ln Metastasis Of Bladmentioning
confidence: 99%
“…The patient characteristics are shown in Supplemental Table 1 (supplemental material available online with this article; https://doi.org/10.1172/JCI96218DS1). As shown in Figure 1A, the microarray analysis identified 158 upregulated and 142 downregulated lncRNAs from 7,419 analyzed lncRNAs in the MIBC tissues, including CASC9, MIAT, MEG3, and LINC01133, which are associated with human cancer progression (25)(26)(27)(28). Additionally, one lncRNA (LINC00958, RefSeq accession number NR_038904), Figure 1.…”
Section: Blacat2 Overexpression Correlates With Ln Metastasis Of Bladmentioning
confidence: 99%
“…lncRNAs have been reported to be involved in a variety of biological processes, including tumorigenesis through regulating oncogenes or tumor suppressors at several levels (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). For example, Xia et al (13) demonstrated that long noncoding RNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) inhibited proliferation and invasion of glioma cells by suppressing the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in 2017, Idogawa et al reported that long non-coding RNA NEAT1 was a transcriptional target of p53 and modulated p53-induced transactivation and tumor-suppressor function (10). Zhou et al demonstrated that downregulation of lncRNA MEG3 mediated by DNMT3b contributed to nickel malignant transformation of human bronchial epithelial cells via modulating PHLPP1 transcription and HIF-1α translation (11). Wang et al uncovered that 2-O-Methylmagnolol upregulated the long non-coding RNA, GAS5, and enhanced apoptosis in skin cancer cells (12).…”
Section: Introductionmentioning
confidence: 99%